1934
DOI: 10.1042/bj0281305
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis of milk

Abstract: Against glycerol. Temp. not stated 25 ml. water (sac). 1000 ml. milk. Time 2 days. Preservative toluene 20 ml. whole milk (collodion sac). 25 ml. water. Time 84 hrs. Temp. "ice-chamber" 25 ml. water (collodion sac). 1000 ml. milk. Time 2 days. Preservative toluene 10 ml. milk (collodion or parchment sac). 5 ml. water. Time 24 hrs. Temp. not stated. Preservative toluene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1956
1956
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…It is known that when milk is heated the concentration of soluble calcium decreases by up to 25% (Lampitt & Bushill, 1934 (1958) consider that the reduction in calcium-ion concentration in evaporated milk is due to the increased binding of calcium by the denatured proteins, a finding in accordance with that of Kannan & Jenness (1956) who showed that increased rennet-coagulation time of heated milk occurred only in the presence of denatured whey proteins.…”
Section: Discussionsupporting
confidence: 54%
“…It is known that when milk is heated the concentration of soluble calcium decreases by up to 25% (Lampitt & Bushill, 1934 (1958) consider that the reduction in calcium-ion concentration in evaporated milk is due to the increased binding of calcium by the denatured proteins, a finding in accordance with that of Kannan & Jenness (1956) who showed that increased rennet-coagulation time of heated milk occurred only in the presence of denatured whey proteins.…”
Section: Discussionsupporting
confidence: 54%
“…Changes in the equilibrium between the colloidal and soluble mineral constituents of milk may also be responsible. For example, a decrease in the pH of milk causes an increase in the concentration of soluble calcium and phosphorus at the expense of the calcium and calcium phosphate content of the caseinate complex (39,40,41,42,43). The citric acid associated with the caseinate complex also passes into the aqueous phase when milk is acidified (44).…”
Section: Introductionmentioning
confidence: 99%
“…The accelerating effect of lactose may be due simply to acidity derived from its decomposition when heated (5,51,52,53) and possibly from its linkage with the basic amino-groups of the caseinate (49). It is well established that when milk is heated the concentrations of soluble calcium and phosphorus decrease (39,54,55,56,57,58,59) and recently the concentration of ionized calcium has also been shown to decrease (60).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1933, scientists were studying the phosphorus content of milk. 2 It is known that milk contains calcium, magnesium, sodium, potas-sium, citrate, chloride, and inorganic phosphate. 3 Many dialysis patients were raised drinking milk and told it was ''good for their bones.''…”
mentioning
confidence: 99%